Sustainable Energy Development, Financial Reporting And Its Attachment To Corporate Social Responsibility - ORBANINGSIH, Dwi (International Journal of Environmental, Sustainability, and Social Science, 2021)
This study intends to examine the impact of Corporate Social Responsibility on the Quality of Financial Reporting and Sustainable Energy Development in manufacturing companies in Indonesia. The research sample has it amounts of 75 manufacturing companies starting from 2017 to 2019. This study uses a regression data panel to examine the effect of Corporate Social Responsibility which is calculated with a dummy variable on the Quality of Financial Reporting. The research results on manufacturing companies in Indonesia show that there is a positive and significant relationship between Corporate Social Responsibility and Financial Reporting Quality and Sustainable Energy Development. The results of this study are expected to benefit practitioners in the operational focus of CSR, which is associated with the quality of financial reporting and does not abandon its energy sustainability development. Furthermore, the results of this study can be used as the basis for forming policies related to sustainable business issues and having a good impact on the environment and the finances of a company.